Innovative Models to Revive the Global Economy Proceedings of the 3rd International Conference on Economics and Social Sciences - Dima, Alina Mihaela (Proceedings of the International Conference on Economics and Social Sciences, 2020)
This conference provides an opportunity for all those interested in Economics and Social Sciences to discuss and exchange research ideas. We welcome both empirical and theoretical work that is broadly consistent with the conference' general theme. Especially, researchers, PhD students and practitioners are invited to submit papers on the topics related to new models in entrepreneurship and innovation, sustainability and education, data science and digitalization, marketing and finance, Fintech & Insurtech etc. that will develop innovative instruments for countries, businesses and education. The innovative models for sustainable development aim to ensure simultaneous economic development, social development, and environmental protection, to achieve a higher quality of life for all people and protect all living beings and the planet.